2003
DOI: 10.1159/000073957
|View full text |Cite
|
Sign up to set email alerts
|

Response of Respiratory-Related Hypoglossal Nerve Activity to Capsaicin-Induced Pulmonary C-Fiber Activation in Rats

Abstract: This study was designed to examine respiratory-related hypoglossal nerve activity in response to activation of pulmonary C-fibers by capsaicin. Rats were anesthetized with urethane (1.2 g/kg, i.p.). Tracheostomy was performed. Catheters were introduced into the femoral vein and artery. Another catheter was placed near the entrance of the right atrium via the right jugular vein. Rats were paralyzed with gallamine triethiodide (5 mg/kg, i.v.), and ventilated artificially. Activities of the phrenic nerve (PNA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
53
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(64 citation statements)
references
References 36 publications
(43 reference statements)
10
53
1
Order By: Relevance
“…The compliance and geometry of this region are influenced by a number of skeletal muscles. Among them are the alae nasi, tongue, and laryngeal muscles, which are innervated by the facial (FN), hypoglossal (HN) and superior (SLN), and recurrent laryngeal nerves (RLN), respectively (1,26,41).Many studies have shown that the inspiratory (I) discharge of the HN precedes the phrenic I burst (5,6,13,17,23,33). This preinspiratory (Pre-I) activity has been suggested to benefit UAW patency by dilating and stiffening the UAW before the onset of I airflow (30).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The compliance and geometry of this region are influenced by a number of skeletal muscles. Among them are the alae nasi, tongue, and laryngeal muscles, which are innervated by the facial (FN), hypoglossal (HN) and superior (SLN), and recurrent laryngeal nerves (RLN), respectively (1,26,41).Many studies have shown that the inspiratory (I) discharge of the HN precedes the phrenic I burst (5,6,13,17,23,33). This preinspiratory (Pre-I) activity has been suggested to benefit UAW patency by dilating and stiffening the UAW before the onset of I airflow (30).…”
mentioning
confidence: 99%
“…Many studies have shown that the inspiratory (I) discharge of the HN precedes the phrenic I burst (5,6,13,17,23,33). This preinspiratory (Pre-I) activity has been suggested to benefit UAW patency by dilating and stiffening the UAW before the onset of I airflow (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Right-atrial injection of capsaicin evoked an inhibitory response of phrenic nerve activity that resulted in reflex apnea appearing as a prolonged TE, as previously described (29,34). This reflex apnea resulted in an increased apneic ratio, reflecting the magnitude of the apneic response.…”
Section: Enhancement Of the Reflex Apnea Response To Chemical Stimulimentioning
confidence: 54%
“…For the studies of apneic reflex, expiratory time (TE) was analyzed as the interval between two successive phrenic bursts (29). The baseline TE was calculated on a breath-by-breath basis as the average value over the 10-breath period immediately before injection of chemical stimulants.…”
Section: Methodsmentioning
confidence: 99%